Combustion performance and emissions of diesel/biodiesel blended fuels in a residential reverse flame boiler. (2017) - Sungur, Bilal; Topaloglu, Bahattin; Namli, Lutfu; Ozcan, Hakan; Ozbey, Mustafa
This paper presents an experimental study on the performance of diesel and biodiesel blended fuels in a water-cooled flame tube boiler. The combustion performance and gas emissions of B10, B20 and B30 were studied and these were compared with the diesel fuel. To investigate the combustion characteristics of biodiesel blends, including pure diesel, the temperature distributions in the combustion chamber and smoke tube, exhaust temperature, and exhaust gas emissions were determined. The results showed that the size of the peak temperature zones in the combustion chamber decreased gradually from B0 to B30. As a consequence of reduced temperatures in combustion chamber, NOx emissions decreased from 53 to 47 ppm and CO emissions increased slightly from 9.6 to 12.8 ppm. Also, CO2 emissions decreased from 13.2 to 12.8 with increasing biodiesel ratio in the diesel fuel. Results also showed that the thermal efficiencies of diesel/biodiesel blended fuels remained almost the same.